Diagnostic Accuracy of Doppler Ultrasonography for the Testicular Torsion in Patients with Acute Scrotum taking Intraoperative Findings as Gold Standard - Muhammad Yaseen Tahir, Hafiz Zaheer Ahmed, Muhammad Hassaan, Bishir Ahmad Noor, Muhammad Zubair, Burhan Rasheed, Usama Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To analyze the diagnostic accuracy of Doppler ultrasonography in detecting acute testicular torsion in patients presenting with acute scrotal pain against the surgical findings as Gold Standard. Material and methods; Cross-sectional study was conducted at the Department of surgery and Radiology of Indus Hospital, Lahore Watim Medical College, Rawalpindi and Niazi Medical and dental college, Sargodha over 6 months. Total 111 males of age 15-45 years having acute scrotal pain (12-48 hours) and testicular torsion diagnosed clinically were enrolled using non-probability-purposive sampling. Doppler ultrasonography was performed on every patient by single radiologist, by using TOSHIBA Just Vision USG machine equipped with curvilinear probe and Doppler USG facilities. Then patients were referred for surgery which was performed by one team, and per-operative findings were documented. Results: Mean age of patients was 29 ± 6.52 years. Average duration of scrotal pain 18.12 ±5.03, average scrotal pain was 7.17 ± 1.50. Forty-three (38.7%) patients had moderate pain, 68 (61.3%) had severe pain. On doppler ultrasonography testicular swelling was seen in 106(95.5%), decreased echogenicity was absent, 100 (90.1%) patients had decreased blood flow. The sensitivity and specificity of doppler ultrasonography was 98.06% and 87.5%, respectively taking surgical findings as gold standard. Positive and negative predictive value of doppler ultrasonography were 99.02% and 77.78% respectively, diagnostic accuracy of Doppler ultrasonography was 97.3% taking surgical findings as gold standard Conclusion: Our finding suggest, this modality of Doppler ultrasonography can be used to detect testicular torsion in patients having acute scrotum as it has reliable sensitivity (98.06%), specificity (87.5%) as well as high diagnostic accuracy (97.3%). Keywords: Scrotal pain, Echogenicity, Testicular swelling, Doppler ultrasonography, Torsion